Lexical-semantic abilities of five-to-six-year-old children - Ana Jegdić; Mile Vuković (Биомедицинска истраживања, 2023)
Introduction: The development of the semantic level of the language system begins at the end of the first year of life, when a child begins to use the first words. During childhood, the child gradually increases his/her vocabulary and learns semantic characteristics. The main aim of this paper is to determine the lexical-semantic abilities of preschool children. Methods: The sample included 50 children of both sexes, aged five to six years. According to age, the respondents were divided into two groups. The first group consisted of five-year-olds, and the second of six-year-olds. The Semantic Test and the Free Word Association Test were used in the research. The semantic test assessed the development of the following categories of words: homonyms, antonyms, synonyms, and metonyms. The free word association test was used to assess the types of responses after a given stimulus word. Results: The results showed that six-year-olds had higher average values compared to five-year-olds on the total score, as well as on individual lexical categories of the Semantic Test. It was also shown that five-year-old girls had higher average values compared to boys of the same age on the Semantic Test. No statistically significant differences were found between five- and six-year-olds in terms of the representation of certain types of answers on the Free Word Association Test. As for sex, it was shown that on the Free Word Association Test, girls had statistically significantly higher number of missing answers compared to boys. Conclusion: It was concluded that the lexical-semantic abilities of preschool children depended on their age, and that there was certain regularity in the development of the semantic features of words and the lexical-semantic structure
Keywords: lexicon; semantics; children